Penerapan biology interactive notebooks dalam flipped classroom untuk meningkatkan hasil belajar biologi - Ayuk Ratna Puspaningsih (Indonesian Journal of Educational Development, 2020)
Flipped Classroom is implemented in Bali Mandara to generate graduates who are able to compete in the 4.0 era. The implementation of the flipped classroom has not been effective yet because of the characteristics of the material, characteristic of students and learning resources so that the learning outcomes are still 4 points below the KKM (passing grade). To accommodate this, biology interactive notebook is applied where there is input on the left which contains notes from the video being studied and output to the right of the results of the construction of knowledge itself from the whole learning process. This is an action research with 3 cycles with metabolic and enzymes, catabolism and anabolism topic on the subjects of 26 people in class XII MIPA 3 of 2019/2020 Academic Year. The results showed that (1) there was an increase in biology learning outcomes and (2) a positive response to the application of biology interactive notebooks because it accommodated the overall learning style, helped organize material, honed metacognition abilities and increased student confidence. Therefore interactive notebooks can be applied to other subjects. Flipped Classroom diterapkan di SMA Negeri Bali Mandara untuk menghasilkan lulusan yang mampu bersaing di era 4.0. Pelaksanaan flipped classroom belum efektif karena karakteristik materi dan peserta didik serta sumber belajar sehingga hasil belajar masih 4 poin di bawah KKM. Untuk mengakomodasi ini diterapkan biology interactive notebooks dimana terdapat input di bagian kiri yang mengandung catatan dari video yang dipelajari dan ouput pada bagian kanan dari hasil kontruksi pengetahuan sendiri dari keseluruhan proses pembelajaran. Ini merupakan penelitian tindakan kelas dengan 3 siklus dengan materi metabolisme dan enzim, katabolisme dan anabolisme pada subjek 26 orang kelas XII MIPA 3 Tahun Pelajaran 2019/2020. Hasil penelitian menunjukkan bahwa (1) ada peningkatan hasil belajar biologi dan (2) respon positif terhadap penerapan biology interactive notebooks karena mengakomodasi keseluruhan gaya belajar, membantu mengorganisasi materi, mengasah kemampuan metakognisi dan meningkatkan kepercayaan diri peserta didik. Oleh karena itu interactive notebooks dapat diterapkan pada mata pelajaran lain.